Ekstrakurikuler Wushu pada Siswa Kelas V Mi Al-Aman Kota Banjarmasin - Hadi, Muhammad Rijali; Suriansyah , Ahmad; Harsono , Arta Mulya Budi; Prihandoko , Yogi; Hidayat, Ari (CV. ITTC INDONESIA, 2024)
Wushu extracurricular is one of the activities in schools that provides opportunities for students to explore their talents. This activity not only helps students develop physical abilities, but also builds self-confidence and cooperation between friends. Thus, wushu extracurricular becomes an ideal place for students to practice and grow holistically. Wushu extracurricular is able to develop an attitude of discipline and responsibility. The researcher conducted this study by applying a qualitative method that focuses on the case study approach. However, the application of this method still shows limitations. Thus, this study relies on the same qualitative method, using a case study approach on students in extracurricular activities at MI Al-Aman, Banjarmasin City. The objectives of the study include: 1) Understanding the Wushu Extracurricular activity system. Data sources come from literature studies, observations, and interviews. The results of the study indicate that wushu extracurricular activities have a positive impact on students, namely developing students' interests, talents, and skills in martial arts.